Measures for the Protection of Intangible Cultural Heritage as Exemplified by the Ritual of Brodacze in Sławatycze - Katarzyna Smyk (Łódzkie Studia Etnograficzne, 2016)
Part one of the article reconstructs the definition of intangible cultural heritage protection, based on the UNESCO Convention of 2003 and the Polish guidelines on applying for registration in the National List of Intangible Cultural Heritage. Part two briefly describes the ritual of brodacze [literally: bearded men] – traditional New Year’s caroling – as practised in Sławatycze (Biała Podlaska district, Lublin province). Part three systematically discusses successive measures aimed at preserving the brodacze ritual that have been taken since the 1980s by the local community cultural centre, local cultural managers and the town authorities in consultation with the depositaries of intangible cultural heritage. In conclusion, the author complements the definition of protection with the elements practised in maintaining the brodacze tradition and poses some problems for consideration: the subjective aspect of heritage protection, the concept of educational measures, and the potential of protective measures practised in Poland.